Clinicopathologic Features of the Non-CNS Primary Ewing Sarcoma Family of Tumors in the Head and Neck Region. Issue 9 (October 2018) - Woo, Chang Gok; Lee, Bora; Song, Joon Seon; Cho, Kyung-Ja
Abstract : Ewing sarcoma family of tumor (ESFT) is a group of malignant neoplasms that affect children and young adults. Primary ESFT does not commonly arise from the head and neck region. This study aimed to elucidate the clinicopathologic characteristics of ESFT of the head and neck region except for central nervous system primitive neuroectodermal tumors. Among the 207 cases of ESFT of the bone and soft tissue, diagnosed at Asan Medical Center during a 20-year period, 25 (12.1%) involved the head and neck region. Of those, 21 were available for histologic, immunohistochemical, and molecular studies. EWSR1 rearrangement was detected in 19 cases by reverse transcriptase-polymerase chain reaction and/or fluorescence in situ hybridization. Primary sites included the cranial area (6 cases, 31.6%), sinonasal tract (6 cases, 31.6%), paraspinal space (4 cases, 21.0%), and other spaces (3 cases, 15.8%). The 5-year overall survival and disease-free survival rates for all cases were 69.7% and 33.6%, respectively. A large tumor size (>5 cm) correlated significantly with overall survival ( P =0.009), but not with disease-free survival ( P =0.210). Microscopically, 8 cases (42.1%) showed nested growth pattern. Clear and/or eosinophilic cytoplasm was observed in 68.4% cases. Immunopositivity for CD99, Friend leukaemia integration-1 (FLI-1), CD57, and caveloin-1 were detected in 100%, 88.9%, 83.3%, and 50% cases, respectively. ESFT in the head and neck region had a favorable prognosis and frequent atypical and epithelioid features. An awareness of these histologic and immunophenotypic characteristics will improve the diagnostic accuracy for head and neck round cell malignancies. Abstract : Supplemental Digital Content is available in the text.